ANALISIS PERBANDINGAN MAKNA WARNA MERAH DALAM PERIBAHASA INDONESIA DAN PERIBAHASA MANDARIN - Chen, Vivi; Ina, Ina; Khiong, Bun Yan (Universitas Tanjungpura, 2023)
Proverbs can use various elements, one of which is color. As part of language, the word color has a specific cultural connotation and symbolic meaning. In different cultures, words of the same color may have the same cultural connotations, but may also have special symbolic meanings. Because China and Indonesia have certain differences in social and cultural backgrounds, psychological thoughts and habits of life, the people of the two countries also have differences in their observation and understanding of color. The author hopes that by comparing the similarities and differences of idioms in the two languages, it will be easier for students to master proverbs. Therefore, the author chose the analysis of the meaning of red in Indonesian and Mandarin idioms as a research. The author collects proverbs related to the color red, there are 15 Indonesian proverbs and 28 Mandarin proverbs. Through analytical research, the author can conclude that in all Indonesian proverbs containing red everything means neutral. In mandarin proverbs that contain a positive meaning there are 28.57%, which contain a neutral meaning there are 67.86%, and then contain a negative meaning there are 3.57%.